Pakistan at the Millennium - Edited by Kennedy, Charles H. [et. al] (Karachi Oxford University Press, 2003)
This collection of studies is presented by a panel of international experts on South Asia. It contains a study of the South Asian nuclear standoff. On the cultural side, long neglected topics such as various strata of music, mysticism and pictorial arts are addressed.
Include Index.
Keywords: Pakistan -- Millennium, Pakistan